2020
DOI: 10.2139/ssrn.3531642
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rates and Political Uncertainty: The Brexit Case

Abstract: This paper studies the impact of political risk on exchange rates. We focus on the Brexit Referendum as it provides a natural experiment where both exchange rate expectations and a time-varying political risk factor can be measured directly. We build a simple portfolio model which predicts that an increase in the Leave probability triggers a depreciation of the British Pound, both on account of exchange rate expectations and of political risk. We estimate the model for multilateral and bilateral British Pound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 31 publications
4
16
1
Order By: Relevance
“…Second, we provide estimates of long-run elasticities of exchange rates with respect to geopolitical risk proxied by the GPR index. This complements similar studies that used different proxies of political risks, such as Manasse et al (2020), Suleman (2017), Bouraoui and Hammami (2017) and Bahmanee-Oskooee et al (2019) who found that political risk was associated with domestic currency depreciation. Third, we provide in-depth assessments on the exchange rates of emerging economies in the ASEAN region which have not been thoroughly covered in the past.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Second, we provide estimates of long-run elasticities of exchange rates with respect to geopolitical risk proxied by the GPR index. This complements similar studies that used different proxies of political risks, such as Manasse et al (2020), Suleman (2017), Bouraoui and Hammami (2017) and Bahmanee-Oskooee et al (2019) who found that political risk was associated with domestic currency depreciation. Third, we provide in-depth assessments on the exchange rates of emerging economies in the ASEAN region which have not been thoroughly covered in the past.…”
Section: Discussionsupporting
confidence: 79%
“…These results are consistent with the findings in the broad literature on the political risk and exchange rate nexus in the sense that political risk tends to harm investors' confidence in the domestic economy resulting in weaker domestic currency value. The theoretical and empirical framework of Manasse et al (2020) The long-run effects of geopolitical risk the risk premium and leads to domestic currency weakening in the context of UK Suleman (2017) found a similar outcome in that higher political risk reduces exchange rate returns in a panel dataset of developed and developing countries. A comprehensive political risk index used by Bouraoui and Hammami (2017) was also shown to undermine the value of the domestic currency in the Arab Spring countries.…”
Section: Findings and Discussionmentioning
confidence: 94%
See 3 more Smart Citations